Cosmeceutical formulation, use thereof and method of preparation thereof - Abd. Gani, Siti Salwa; Bidin, Hasmah; Basri, Mahiran; Abd. Malek, Emilia (2014)
The present invention provides a cosmeceutical formulation containing the Pitaya plant Hylocereus polyrhizus seed extracts comprising polyphenols and/or fatty acid compounds, its use as antioxidant and moisturizing skin preparation, as well as a method for preparation thereof.